Heat Transfer in Diesel and Partially Premixed Combustion Engines; A Computational Fluid Dynamics Study. Issue 17 (22nd November 2017) - Fridriksson, Helgi; Sundén, Bengt; Tunér, Martin; Andersson, Öivind
ABSTRACT: This article presents findings from a Computational Fluid Dynamics (CFD) study performed on the heat transfer characteristics of diesel and partially-premixed combustion (PPC) engines. The study is confined to the combustion bowl, where numerical simulations have been performed on a part of the engine cycle, namely the compression, combustion, and expansion phases. Three engine geometries were simulated and after validating the results with experimental data, parameter variations were carried out, in order to estimate their effects on the heat transfer, engine performance, and emission levels. The work was performed using a commercial CFD tool, with which only a part of the engine cylinder was modeled, the enclosure of one spray. The results highlight some important characteristic differences between the conventional diesel combustion and the low-temperature combustion scheme PPC. The reduced in-cylinder temperatures for the PPC case lead to a reduced production of NOx and soot emissions, without compromising the engine performance, only a small penalty in the increased intake air pressure is found. The importance of an appropriate injection strategy was also highlighted, as the presence of a pilot injection during the compression stroke enhanced the temperature stratification in a PPC engine. This leads to reduced heat losses and improved engine efficiency. Finally, the shape of the combustion bowl was shown to have significant effects on both heat losses as well as emission levels.